2007
DOI: 10.1007/s10494-007-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Turbulent Thermal Mixing of Hot and Cold Airflows in T-junction

Abstract: An experimental study has been conducted on the promotion and control of turbulent thermal mixing of hot and cold airflows in a T-junction with rectangular cross sections, which simulates the HVAC unit for automobile air-conditioning system. In order to promote the turbulent thermal mixing, small jets have been blown into the main channel at the upstream edge of the T-junction in the direction of 45°against the main flow. Turbulence intensity in the upper part of the thermal mixing layer can be increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…According to Hirota et al (2008), the velocity distributions measured under the isothermal condition agreed with those obtained with T h =60 o C and T c =12 o C, suggesting that the buoyancy effect on the mixing is negligibly small. In this study, the temperature difference is 17 o C so the present treatment of the temperature is reasonable.…”
Section: Numerical Detailssupporting
confidence: 78%
“…According to Hirota et al (2008), the velocity distributions measured under the isothermal condition agreed with those obtained with T h =60 o C and T c =12 o C, suggesting that the buoyancy effect on the mixing is negligibly small. In this study, the temperature difference is 17 o C so the present treatment of the temperature is reasonable.…”
Section: Numerical Detailssupporting
confidence: 78%
“…In this channel geometry, the heat transfer between the hot and cold airflows is dominated by the turbulent heat flux vt and its main production term is expressed as v 2 T/Y. Therefore, the production of vt is quite small in the upper part of the thermal mixing layer (Hirota, et al, 2008) and this causes such a limited development of the thermal mixing layer in the upward direction as observed in Fig. 6.…”
Section: Which (T-t C )/(T H -T C ) = 01 (Upper Boundary Of the Thermentioning
confidence: 96%
“…The specification of this channel was essentially the same as that used in our preceding study (Hirota, et al, 2010) except that the second edge (edge in the downstream side) of the T-junction was planed off. We chamfered this second edge because high turbulence caused by the flow separation at this sharp edge was located below the thermal mixing layer, and did not contribute so much to the turbulent thermal mixing of two flows (Hirota, et al, 2008). By chamfering this edge, the scale of the separation bubble was considerably reduced.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have investigated flows in T-junctions experimentally in the past. Hirota et al [5] investigated the improvement in thermal mixing of hot and cold fluid flows in a T-junction. They concluded that the turbulence in the upper part of the mixing layer could be improved by blowing the jets through the main pipe at the upstream edge of the T-junction.…”
Section: Introductionmentioning
confidence: 99%